Effect of temperature on the reproductive success, developmental rate and brood characteristics of Ips sexdentatus (Boern.). (10th August 2016) - Pineau, Xavier; David, Guillaume; Peter, Zsuzsanna; Sallé, Aurélien; Baude, Mathilde; Lieutier, François; Jactel, Hervé
Abstract: Global warming is predicted to enhance the development rate and increase the number of generations in multivoltine insects. For secondary forest pests, such as the pine bark beetle Ips sexdentatus, the resulting increase in population level could trigger more frequent outbreaks. However, this positive effect could be outweighed by a temperature‐dependent decrease in offspring quality. To test these hypotheses, we carried out a laboratory rearing experiment with maritime pine logs at six temperature regimes reproducing hourly fluctuations and averaging 12–25.5 °C. We estimated the thermal requirements for a complete development of the beetle and the number of offspring per female. The offspring quality was estimated using three traits: dry body weight, elytra length and lipid content. The minimum and maximum developmental threshold were estimated at 10.9 and 36 °C, respectively, and the thermal requirements for complete development were estimated at 517 degree‐days. We predicted a mean of two generations per year in southwestern France, although an additional generation could occur during warmer years. The number of offspring increased exponentially with temperature, although we observed a curvilinear response of offspring traits to temperature, with optima at 15–18 °C. This suggests that there are trade‐offs between productivity and quality of offspring. Global warming is therefore likely to result in higher number of generations of I. sexdentatus per year, with larger broods but of reduced fitness at high temperatures.